ФОРМУВАННЯ ВХІДНОГО СТРУМУ МАТРИЧНОГО ПЕРЕТВОРЮВАЧА У КОВЗНОМУ РЕЖИМІ ПРИ НЕСИМЕТРІЇ НАПРУГ ЖИВЛЕННЯ - Мисак , Т.В.; Михальський , В.М. (Інститут електродинаміки НАН України, Київ, 2015)
The object of study is a matrix converter with input LC-filter, controlled in sliding mode, if there is a three-phase voltage unbalance supply. The synthesis of sliding mode in the implementation strategy of zero phase shift in the control of the input current. Using Lyapunov functions allowed to derive an equation for the sliding surface. Conditions for the existence of the sliding mode depending on the degree of asymmetry is obtained. The influence of voltage unbalance on the load current and input current characteristics is investigated. The results of the simulation is described. References 4, figures 5.